Respuesta :

The fourth and last are correct.


One you have and exponent of an exponent, the base stays the same and the exponents get to be multiplyied:


[tex] \bf~(y^{x})^{z} = y^{xz} [/tex]


Both -8 x -2 and 8 x 2 equal 16.


Answer:


[tex] \boxed{\bf~The~fourth~and~last~options~are~correct.} [/tex]



Hope it helped,


Happy homework/ study/ exam!

Answer:

[tex](6^{-4})^{-4}=(6^{-2})^{-8}=(6^{8})^{2}=6^{16}[/tex]

Step-by-step explanation:

Given: [tex]6^{16}[/tex]

We need to correct option equivalent to [tex]6^{16}[/tex]

#1 [tex](6^0)^{16}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^0)^{16}=6^{0\times 16}\Rightarrow 6^0\neq 6^{16}[/tex]

False

#2 [tex](6^8)^{8}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^8)^{8}=6^{8\times 8}\Rightarrow 6^{64}\neq 6^{16}[/tex]

False

#3 [tex](6^{-4})^{-4}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^{-4})^{-4}=6^{-4\times -4}\Rightarrow 6^{16}= 6^{16}[/tex]

True

#4 [tex](6^{-2})^{-8}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^{-2})^{-8}=6^{-2\times -8}\Rightarrow 6^{16}= 6^{16}[/tex]

True

$5 [tex](6^{-1})^{16}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^{-1})^{16}=6^{-1\times 16}\Rightarrow 6^{-16}\neq6^{16}[/tex]

False

$6 [tex](6^{8})^{2}[/tex]

Using exponent property, [tex](a^m)^n=a^{mn}[/tex]

[tex](6^{8})^{2}=6^{8\times 2}\Rightarrow 6^{16}= 6^{16}[/tex]

True

Hence,   [tex](6^{-4})^{-4}=(6^{-2})^{-8}=(6^{8})^{2}=6^{16}[/tex]